The Effect of Ethical Orientation and Ethical Knowledge on Organizational Behavior with Gender as An Intervening Variable - Tohawi, Agus (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to determine and analyze the influence of ethical orientation and ethical knowledge on organizational behavior with gender as an intervening variable at one of the universities in Indonesia. The research method is quantitative with an explanatory research approach with a survey approach. The questionnaire was prepared based on research variables: ethical orientation, ethical knowledge, organizational behavior, and gender. Research data was taken from 100 students who were the samples for this research. Data collection was carried out using random sampling techniques. This research analyzes data using multiple regression analysis. The research results show that ethical orientation positively affects organizational behavior. The higher the ethical orientation, the higher the organizational behavior. In addition, ethical orientation also influences gender, with a positive relationship between ethical orientation and gender. Likewise, gender positively affects organizational behavior; the higher the gender, the higher the organizational behavior. Ethical knowledge also influences organizational behavior positively. The higher the ethical knowledge, the higher the organizational behavior. Furthermore, ethical knowledge affects gender, showing a positive correlation between ethical knowledge and gender. However, the findings show that ethical orientation does not directly influence organizational behavior through gender, indicating the absence of a mediation effect. In contrast, ethical knowledge indirectly influences organizational behavior through gender, suggesting a mediation effect. Therefore, gender can act as a mediating variable between ethical knowledge and organizational behavior.